Aplikasi Layanan Olsera Sebagai Pengatur Manajemen Keuangan Auf Store Distro Muslim Karawang - Diktia Nurfadilah; Alfanny Alfanny; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Universitas 45 Surabaya, 2023)
The purpose of this paper is to find out what the trading company's financial management system is like and to find out what obstacles a trading company faces when using the Olsera financial management application. This writing is motivated by the importance of financial management for trading companies. Most trading companies, including a Muslim distribution company called Auf Store Muslim Distro Karawang, keep financial records through an application, namely Olsera, which records daily income and expenses, making it easier to manage transactions and simplify financial management. Good financial management can provide accurate information about the financial status of a trading company. The type of writing chosen by the writer is descriptive and observational research, that is, a writing method that is carried out with the main objective being to create an objective picture of a situation. This writing was done in the stages of data collection, classification, data analysis and drawing conclusions. This observation was carried out at the interview stage which the author conducted with the owner of a trading company, namely Auf Store Distro Muslim Karawang. The results of the discussion and the contents of the financial management policy for the trading company Auf Store Distro Muslim Karawang, the financial records have been computerized using the financial management regulatory service application, namely Olsera.